Effects of posture-related auditory cueing (PAC) program on muscles activities and kinematics of the neck and trunk during computer work. - Yoo, Won-Gyu; Park, Se-Yeon (Work, 2015)
BACKGROUND: The etiology of the neck and back discomfort are highly associated with abnormal static posture such as forward head posture and flexed relaxed posture; such postures are regarded as the risk factors for work-related musculoskeletal disorders. Although, various ergonomic chairs and devices have been developed for computer workers, there are few reports of software that can alert users to their posture or work hours. OBJECTIVE: Purpose of the present study was to investigate the difference of kinematics of the neck and trunk segments as well as muscular activation between condition with and without posture related auditory cueing. METHODS: Twelve male computer workers were recruited in this study. A posture related auditory cueing (PAC) program used a media file that generated postural correction cue at intervals of 300 seconds. Surface electromyography was used to measure the activity of the erector spine and upper trapezius. Kinematic data were obtained using an ultrasonic three dimensional movement analysis system. RESULTS: The results showed that the means of trunk flexion and forward head angle were significantly reduced with PAC. The muscular activity of the erector spine and upper trapezius was significantly higher with the PAC and significantly lower without the PAC.CONCLUSIONS: Our findings suggested that the software providing PACs is an ergonomic device with positive effects for preventing habitual poor posture and potential for widespread practical usage.